2022
DOI: 10.1186/s12913-022-08370-y
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the assessment process within telerehabilitation in chronic diseases: a scoping meta-review

Abstract: Background Telerehabilitation (TR) interventions are receiving increasing attention. They have been evaluated in various scientific areas through systematic reviews. However, there is a lack of data on how to standardize assessment and report on their domains to guide researchers across studies and bring together the best evidence to assess TR for chronic diseases. Aims and objectives The aim of this study was to identify domains of assessment in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 129 publications
0
1
0
Order By: Relevance
“…125 An SR revealed that these domains were not assessed in studies of telerehabilitation in a balanced way with a focus on clinical effectiveness, social aspects in terms of behavioral changes in most of the studies, and safety was assessed the least. 126 …”
Section: Discussionmentioning
confidence: 99%
“…125 An SR revealed that these domains were not assessed in studies of telerehabilitation in a balanced way with a focus on clinical effectiveness, social aspects in terms of behavioral changes in most of the studies, and safety was assessed the least. 126 …”
Section: Discussionmentioning
confidence: 99%